The wire games. A gaming experience within a Grade Class - Antonio Montero-Navarro; José-Luis Rodríguez-Sánchez; Rocio Gallego-Losada; Thais González-Torres (WPOM : Working Papers on Operations Management)
This work describes in detail the development of an educational game as a tool to check the degree of acquisition and consolidation of knowledge of the student in relation to a subject are . It is proposed as a complementary method to traditional methodologies. Thus, the article presents the devolpment of a brand new serious game which has been created in the 2019-20 academic year. Ithas been used in two different groups of the Degree in Business Management (one taught in English and the other one in Spanish). Based on previous gamification experiences, the design and use of the game has lead to the achievement of the goals pursued, generating also an important volume of valuable information that can increase the effectiveness of the use of other tools (tutorials, theoretical immersion in some specific subjects or case studies).